2023
DOI: 10.3390/ijerph20053906
|View full text |Cite
|
Sign up to set email alerts
|

Activities Carried Out during the First COVID-19 Lockdown by Italian Citizens

Abstract: The SARS-CoV-2 pandemic has altered how citizens engage in activities. This study describes the new activities citizens engaged in during the first lockdown, factors that helped them cope with the confinement, the supports they used the most, and which supports they would have liked to receive. This cross-sectional study consists of an online survey made of 49 questions that was completed by the citizens of the province of Reggio Emilia (Italy) from 4 May until 15 June 2020. The outcomes of this study were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Previous studies performed in Europe showed that in the prepandemic period (i.e., before the lockdown), (i) 89% of OAs showed an interest in quiet leisure occupations [ 11 ] and (ii) 18% of European adults aged 50 and over engaged in quiet leisure more than once a week (22% in France), vs. 9% for people below the age of 50 (8% in France) [ 23 ]. Our univariate analysis showed that reading was the most frequent quiet leisure occupation, which is in line with Paltrinieri et al's report that 39% of the surveyed citizens in Reggio Emilia read more than before [ 19 ]. In our study, this was especially true among OAs.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Previous studies performed in Europe showed that in the prepandemic period (i.e., before the lockdown), (i) 89% of OAs showed an interest in quiet leisure occupations [ 11 ] and (ii) 18% of European adults aged 50 and over engaged in quiet leisure more than once a week (22% in France), vs. 9% for people below the age of 50 (8% in France) [ 23 ]. Our univariate analysis showed that reading was the most frequent quiet leisure occupation, which is in line with Paltrinieri et al's report that 39% of the surveyed citizens in Reggio Emilia read more than before [ 19 ]. In our study, this was especially true among OAs.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that adults of all generations started or developed several leisure activities during lockdown. This finding is in line with (i) Paltrinieri et al's report in which 84% of the surveyed citizens in the Italian province of Reggio Emilia started new leisure occupations during lockdown [ 19 ] and (ii) Huls et al's [ 20 ] report that respondents spent 11% more time on leisure. More precisely, quiet recreations (typically those practiced at home) accounted for 38% of the 4500 newly performed or more frequently performed occupations in our study; this was especially true for YAs after adjustment for other sociodemographic variables.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations